Differences in longissimus thoracis metabolites in feedlot steers with differing plasma Zn concentration and implant status - Ortner, Brock M.; Smerchek, Dathan T.; Hansen, Stephanie L. (Frontiers in Animal Science, 2025)
This study examined the role of Zn status on muscle glucose and other metabolites. Angus steers (144; 525 ± 30 kg) with varying plasma Zn concentrations and implant status were used for this secondary experiment. Steers were assigned to implant (IMP) treatments: no implant (NO) or Component TE-200 (TE-200; Elanco, Greenfield, IN) on d 0. Zinc sulfate was supplemented at 0 (analyzed 54 mg Zn/kg DM), 30, or 100 mg Zn/kg DM starting d -60. Steers were fed in two blocks via GrowSafe bunks, and steer was the experimental unit. Jugular blood and longissimus thoracis biopsies were collected d 40 post-implant. Plasma Zn was quantified via ICP-OES and stratified into quintiles by concentration and IMP treatment. Samples (n = 48; 12 low and 12 high from each IMP group) were identified and designated to plasma Zn treatments (PLZN): low (LO, 1.1 mg Zn/L) or high (HI, 1.6 mg Zn/L). Corresponding muscle samples were analyzed via gas chromatography-mass spectrometry for non-targeted metabolomics. Data were analyzed using ProcMixed of SAS with fixed effects of PLZN, IMP, BLOCK, and PLZN×IMP. No interactions were noted. β-alanine, 3-hydroxybutyric acid, and glycine were greater in HI than LO (P ≤ 0.05), while 3-hydroxybutyric acid, 2,3,4-trihydroxybutyric acid, and glycine were greater in TE200 than NO (P ≤ 0.03). Lactic and malic acids tended to be greater in TE200 than NO (P ≤ 0.10). Although both Zn groups were adequate, greater plasma Zn altered metabolites indicative of enhanced energy metabolism, potentially explaining benefits of Zn supplementation to feedlot cattle.